Impact of cinnamon consumption on serum glycemia in patients with Type 2 Diabetes Mellitus: Review of the literature - Cadavid-Serna, Mariana Lucía (2023)
Introduction: Type 2 DM is considered one of the most prevalent chronic noncommunicable diseases worldwide. The treatment of this disease includes non-pharmacological measures, with diet being a key focus. One potentially relevant dietary component is cinnamon, which contains bioactive compounds that could contribute to glycemic control. Given the clinical potential demonstrated by cinnamon, the objective of this review is to determine its possible impact on serum glycemia in patients with type 2 DM. Materials and methods: We conducted a literature review using information from the PubMed, Science Direct, and Google Scholar databases. We included articles published between 2006 and 2022 in our review and meta-analysis. These articles contained information on the clinical evidence of cinnamon consumption and its impact on relevant clinical markers such as blood glucose, lipid profile, and BMI. Results: Our review of the collected information suggests that the components of cinnamon may play a role in the insulin signaling process and that the consumption of cinnamon could lead to reduced glycemia levels in patients who are already undergoing pharmacological management. Additionally, our findings indicate that cinnamon consumption in these patients did not result in adverse effects or worsen the disease. Conclusion: Although studies documenting the impact of cinnamon on serum glycemia have been reported, there is still insufficient evidence to definitively confirm cinnamon as a hypoglycemic factor. Nevertheless, the evidence we found does not preclude the use of cinnamon as an adjunctive therapy for patients with type 2 DM.